WR-32AB : flooding modelling studies - use of RainSim - Koh, Jocelyn Seow Mian (2014)
RainSim V3 is a robust and well-tested stochastic rainfall field generator that uses a Spatial Temporal Neyman-Scott Rectangular Pulses (STNSRP) process. In this project, it was used to generate rainfall simulations for the 3 calibration/verification cases at Jakarta, Indonesia. The purpose of it was to assess how well RainSim V3 simulated rainfall in Jakarta by further looking into the accuracy and reliability of the simulated data.